Mandibular development in Australopithecus robustus. Issue 3 (13th May 2014) - Cofran, Zachary
ABSTRACT Australopithecus robustus has a distinct mandibular anatomy, with a broad and deep corpus and a tall, relatively upright ramus. How this anatomy arose through development is unknown, as gross mandibular size and shape change have not been thoroughly examined quantitatively in this species. Herein, I investigate A. robustus mandibular growth by comparing its ontogenetic series with a sample of recent humans, examining age‐related size variation in 28 linear measurements. Resampling is used to compare the amount of proportional size change occurring between tooth eruption stages in the small and fragmentary A. robustus sample, with that of a more complete human skeletal population. Ontogenetic allometry of corpus robusticity is also assessed with least squares regression. Results show that nearly all measurements experience greater average increase in A. robustus than in humans. Most notably, A. robustus corpus breadth undergoes a spurt of growth before eruption of M1, likely due in part to delayed resorption of the ramus root on the lateral corpus. Between the occlusion of M1 and M2, nearly all dimensions experience greater proportional size change in A. robustus. Nested resampling analysis affirms that this pattern of growth differences between species is biologically significant, and not a mere byproduct of the fossil sample size. Some species differences are likely a function of postcanine megadontia in A. robustus, although the causes of other differences are less clear. This study demonstrates an important role of the postnatal period for mandibular shape development in this species. Am J Phys Anthropol 154:436–446, 2014. © 2014 Wiley Periodicals, Inc.